The Political Economy of Healthcare Litigation : Model and Empirical Application to Uruguay - Corduneanu-Huci, Cristina; Hamilton, Alexander; Masses-Ferrer, Issel (2012)
The political economy of health care is complex, as stakeholders have conflicting preferences over efficiency and equity. This paper formally models the preferences of consumer and producer groups involved in priority setting and judicialization in public health care. It uses a unique dataset of stakeholder perceptions, from Uruguay, to test whether these hypotheses are consistent with empirical evidence. The results suggest that the expectations of the political economy literature are supported: 1) regulators of public healthcare are less concerned with efficiency considerations than consumers; and 2) less organized groups are more concerned about equity than more organized interest groups. With respect to the consequences of health litigation, the findings are only partially consistent with the health care governance literature. Consumers perceive litigation as more beneficial than health care providers and regulators do. Counter-intuitively, powerful interest groups seem less willing to use litigation to shape policy outcomes.